Knowledge, Art, and Power : An Outline of a Theory of Experience - Ryder, John (Value Inquiry Book Series, 2020)
In Knowledge, Art, and Power: An Outline of a Theory of Experience John Ryder presents an original theory of experience rooted in the American pragmatic naturalist philosophical tradition. The operative assumption of the book is that a clearer understanding of experience provides a richer conception of human being. Beginning with the Deweyan idea of experience as the mutually constitutive engagement of an individual with her environing conditions, the theory posits that there are three general dimensions that condition all of our experience - cognitive (knowledge), aesthetic (art), and political (power). All other constituents and forms of experience, such as language, emotions, ethics, religion, and others, are conditioned by these three general threads that define the fabric of experience and of human life.